2017
DOI: 10.1631/jzus.b1700308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucose and gibberellic acid on glucosinolate content and antioxidant properties of Chinese kale sprouts

Abstract: Glucosinolates, anthocyanins, total phenols, and vitamin C, as well as antioxidant capacity, were investigated in Chinese kale sprouts treated with both glucose and gibberellic acid (GA 3 ). The combination of 3% (0.03 g/ml) glucose and 5 μmol/L GA 3 treatment was effective in increasing glucosinolate content while glucose or GA 3 treatment alone did not influence significantly almost all individual glucosinolates or total glucosinolates. The total phenolic content and antioxidant activity of Chinese kale spro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…The sprout extracts of Chinese kale ( B. oleracea var. alboglabra ) exhibited antioxidant activity [ 70 ]. Raphasatin in radish sprouts was also identified to be more potent as a chemopreventive compound than its corresponding GSHP [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sprout extracts of Chinese kale ( B. oleracea var. alboglabra ) exhibited antioxidant activity [ 70 ]. Raphasatin in radish sprouts was also identified to be more potent as a chemopreventive compound than its corresponding GSHP [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Exogenous application of phytohormones triggers/manipulates GSs, GSHPs, and their related gene expression profiles. Among the phytohormones used include methyl jasmonic acid (MeJA) [ 164 ], gibberellic acids (GA3) in combination with glucose [ 70 ] and jasmonic acid (JA) [ 165 ]. A 250 µM MeJA spray treatment on Brassica napus var.…”
Section: Benefits Of Natural and Synthetic Gss And Gshpmentioning
confidence: 99%
See 1 more Smart Citation
“…The study indicated that salicylic acid combined with chitosan-treated sprouts enhanced the phenolic compounds and antioxidant activity higher than individual treatments. Higher GL, anthocyanin, phenolic compounds, and vitamin C content were also observed when Chinese kale sprouts were treated with glucose and gibberellic acid [ 126 ]. Hence, the hurdle approach can be an effective mechanism to improve the functional property of seeds.…”
Section: Recent Novel Approach For Enhancing Biological Activities Of Sproutsmentioning
confidence: 99%
“…Between 2011 and 2012, E. coli O26 infection associated with sprouts occurred, with the clover sprouts prepared from contaminated seeds reported as the major culprit [ 130 , 131 ]. Physical treatments and chlorine-based compounds have been proposed to improve the microbial safety of sprouts [ 126 ]. Thus, due to inability to completely eradicate pathogens from these products, sprouts have become the major fresh products associated with food infection [ 132 , 133 , 134 ].…”
Section: Microbial Safety Of Sproutsmentioning
confidence: 99%